The Relevance And Implications Of Metacognitive Strategy To Reading Comprehension In EFL Classroom - Eka Rizki Amalia (STAI Miftahul Ula Nganjuk, 2018)
Metacognitive strategy plays a significant role in solving students’ problem in learning English as a foreign language by being applied to some teaching and learning activities. Its strength is on realizing and optimizing students’ awareness upon their own learning. By perceiving their own knowledge, students have control of what they have in mind and can regulate it to achieve certain purposes. This is how they can maximize their learning. In reading skill, students are always demanded to understand the texts they are reading. Thus, applying metacognitive strategy to reading activity will foster the students’ comprehension respectively. This literature review discusses the relevance and implications of metacognitive strategy to reading comprehension in EFL classroom.